What is the role of motif D in the nucleotide incorporation catalyzed by the RNA-dependent RNA polymerase from poliovirus? - Hujun Shen; Hui Sun; Guohui Li (PLoS Computational Biology)
Poliovirus (PV) is a well-characterized RNA virus, and the RNA-dependent RNA polymerase (RdRp) from PV (3D(pol)) has been widely employed as an important model for understanding the structure-function relationships of RNA and DNA polymerases. Many experimental studies of the kinetics of nucleotide incorporation by RNA and DNA polymerases suggest that each nucleotide incorporation cycle basically consists of six sequential steps: (1) an incoming nucleotide binds to the polymerase-primer/template complex; (2) the ternary complex (nucleotide-polymerase-primer/template) undergoes a conformational change; (3) phosphoryl transfer occurs (the chemistry step); (4) a post-chemistry conformational change occurs; (5) pyrophosphate is released; (6) RNA or DNA translocation. Recently, the importance of structural motif D in nucleotide incorporation has been recognized, but the functions of motif D are less well explored so far. In this work, we used two computational techniques, molecular dynamics (MD) simulation and quantum mechanics (QM) method, to explore the roles of motif D in nucleotide incorporation catalyzed by PV 3D(pol). We discovered that the motif D, exhibiting high flexibility in either the presence or the absence of RNA primer/template, might facilitate the transportation of incoming nucleotide or outgoing pyrophosphate. We observed that the dynamic behavior of motif A, which should be essential to the polymerase function, was greatly affected by the motions of motif D. In the end, through QM calculations, we attempted to investigate the proton transfer in enzyme catalysis associated with a few amino acid residues of motifs F and D.